Causal Association Between mTOR-Dependent eIF4E mRNA Cap-Dependent Translation and Type 2 Diabetes: A Mendelian Randomization Study (OR31-02-19). (13th June 2019) - Soliman, Ghada; Schooling, C Mary
Abstract: Objectives: Type 2 diabetes is a prevalent chronic disease and is often associated with obesity and other comorbidities. The mammalian Target of Rapamycin complex 1 (mTORC1) nutrient-signaling pathway is a central regulator of cell growth and metabolism and is dysregulated in chronic diseases including diabetes and obesity. The eukaryotic translation initiation factor 4E (eIF-4E), a key regulator of gene translation and protein function, is under the control of mTOR and eIF4E Binding Proteins (4E-BPs). eIF-4E binds to the m7G (7-methylguanosine) cap at the 5'-UTR of most eukaryotic mRNA and mediates the recruitment of mRNA on ribosomes to start the protein translation. Both 4E-BP and ribosomal protein S6K kinase (S6K) are downstream effectors regulated by mTORC1 but converge to regulate two independent pathways. We investigated whether the risk of type 2 diabetes varied with genetically predicted eIF-4E and S6K levels using Mendelian Randomization (MR). Methods: We estimated the causal role of eIF-4E and S6K plasma proteins, mTOR downstream targets, on type 2 diabetes, based on 16 single nucleotide polymorphisms (SNPs) for eIF-4E and 16 SNPs for S6K at P -value < 5x10 −6 . We applied these SNPs per exposure to publically available genetic associations with diabetes from the DIAbestes Genetics Replication And Meta-analysis (DIAGRAM) case ( n  = 26, 676), and control ( n  = 132, 532) study (mean age 57.4 years). We meta-analyzed SNP-specific Wald estimates using inverse variance weighting with multiplicative random effects. Sensitivity analysis was conducted using the weighted median, and MR-Egger estimates. Results: eIF-4E cap-dependent translation factor was associated with lowered risk of type 2 diabetes with an odds ratio (OR) 0.94 per effect size, 95% confidence interval (0.88, 0.99, P  = 0.03) with similar estimates from the weighted median and MR-Egger. S6K was not associated with diabetes, OR 0.95, 95% confidence interval (0.89, 1.01, P  = 0.08). Sensitivity analysis using MR-Egger and weighed median analysis did not indicate pleiotropic effects suggesting a unique protective effect of eIF-4E on type 2 diabetes. Conclusions: This unbiased Mendelian Randomization estimate is consistent with a causally protective association of eIF-4E on type 2 diabetes. eIF-4E may be a target for intervention by repurposing existing therapeutics to reduce the risk of type 2 diabetes. Funding Sources: No specific funding.